Uncovering the motivating learning approaches for Massive Open Online Courses (MOOCs) - Nur Farahanim, Zainuddin (Universiti Malaysia Sarawak (UNIMAS), 2018)
Massive Open Online Courses (MOOCs) is a unique open learning platform that offers free and open access to all learners around the globe. Uniquely, MOOCs nowadays become a popular trend in the education field, either for distance learning or open learning and it acts as a new technology that can enhance learning. Many studies reveal that MOOCs have low retention rate and high drop-out rate. The purpose of this study is to uncover the learning approaches that motivate learners to learn in MOOCs based on ARCS motivational model which stands for Attention, Relevance, Confidence, and Satisfaction. The Fuzzy Analytic Hierarchy Process Approach (FAHP) was used as the main methodology for this study. This study involved 200 participants. The study has revealed the most motivating learning approaches for each motivation dimension proposed by the ARCS motivational model. Based on these findings, strategies to implement motivating learning approaches in MOOCs are recommended.